Asuhan Kebidanan Pada Ibu Pasca Persalinan Di PMB Erida Rismayanti Wilayah Kerja Puskesmas Laboy Jaya Tahun 2022 - Nursyafitri, Reza; Syahda, Syukrianti (Evidence Midwifery Journal, 2023)
Post delivery is a critical period where there is a series of changes in mothers that have an impact on physical, psychological and social. To optimize the health of maternal and infants, postpartum care must be a sustainable process, with care and support that is tailored to the needs of each postpartum mother so that the care provided can help mothers through their childbirth. Post -delivery care consists of monitoring and inspection. The examination material includes measuring the body temperature and pulse of the mother of maternity, recording blood pressure, examining breasts, examining uterine involution, monitoring Lochea. The purpose of this case is to find out the midwifery care given to Mrs. in the suture wound area. From the results of this study it is hoped that mothers in postpartum in order to always maintain the cleanliness of the perineum that has been done well. Thus the care given to the patient goes well